1989
DOI: 10.1016/0014-5793(89)80709-4
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of a functional fucose‐specific lectin from an orange peel mushroom, Aleuria aurantia

Abstract: Aleuriu auruntia lectin (AAL) shows sugar-binding specificity for L-fucose. A lgtl 1 expression library was constructed from A. aurantiu poly(A) RNA and screened with a polyclonal antiserum directed against AAL. An immunopositive clone carrying 1.3-kb EcoRI fragment was obtained. The fragment encoded AAL, but lacked a nucleotide sequence corresponding to the two amino-terminal amino acids. The S-terminal part of the fragment was replaced with a chemically synthesized DNA fragment and inserted into an expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Lectin, the pattern recognition protein (PRP) recognizing and binding to terminal sugars on glycoproteins and glycolipids, is one of the major components in these host-defence systems [2]. It has been isolated and characterized from viruses [3], bacteria [4], fungi [5,6], plants [7,8], and animals [2,9,10]. Among the lectin of invertebrates origin, sialic acid binding lectins (SABL) show attractive attention for their potentially roles in glycobiology or cancer research such as detection, localization, and isolation of sialoglycoconjugates [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lectin, the pattern recognition protein (PRP) recognizing and binding to terminal sugars on glycoproteins and glycolipids, is one of the major components in these host-defence systems [2]. It has been isolated and characterized from viruses [3], bacteria [4], fungi [5,6], plants [7,8], and animals [2,9,10]. Among the lectin of invertebrates origin, sialic acid binding lectins (SABL) show attractive attention for their potentially roles in glycobiology or cancer research such as detection, localization, and isolation of sialoglycoconjugates [11].…”
Section: Introductionmentioning
confidence: 99%
“…Later, the primary sequence was determined and demonstrated the presence of six internal repeats of about 50 amino acids (16). Cloning of the gene allowed production of the recombinant lectin in Escherichia coli (17). Further characterization of the lectin specificity demonstrated that all fucose-containing disaccharides present on glycoconjugates (␣Fuc1-2Gal, ␣Fuc1-3GlcNAc, ␣Fuc1-4GlcNAc, and ␣Fuc1-6GlcNAc) displayed similar binding to the lectin, higher than that shown for highly branched oligosaccharides such as the determinants of Lewis histo-blood groups (15,18,19).…”
mentioning
confidence: 99%
“…We have investigated the structure of AAL by cloning cDNA 6,7) and genomic DNA, 8) and by crystallization. 9) In this report we describe production of a large amount of functional AAL in Pichia pastoris, a methylotrophic yeast, and found that AAL produced in this yeast was glycosylated, and acquired higher thermostability.…”
Section: )mentioning
confidence: 99%
“…pastoris GS115 (His4 -) and plasmid pPIC9K were purchased from Invitrogen (Carlsbad, USA). An expression plasmid, pPIC9K-AAL, was constructed as follows: Because of the existence of two XhoI-recognition-sites in the plasmid pPIC9K, a BamHI-EcoRI fragment (288 bp) containing one XhoI site was introduced into pUC19, and the cloned AAL gene 6) was inserted into the XhoI-EcoRI site of the plasmid. The resultant BamHI-EcoRI fragment was cleaved from the plasmid, and then inserted into pPIC9K.…”
Section: )mentioning
confidence: 99%